Enhancing institutional support to ensure timely PhD completions in law - Jade Lindley; Natalie Skead; Michael Montalto (Legal Education Review)
Doctor of Philosophy (‘PhD’) students in Australia undertake at least three years of full-time equivalent independent research to generate innovative knowledge within their chosen discipline. Research indicates, however, that globally half of all enrolled PhD students fail to complete. For those who do complete, despite the increasing imposition of academic milestones and supervisory requirements, many require an extension or an approved period of interruption of their candidature. While attracting and retaining high-quality PhD students who complete their research project within the required timeframe is an institutional priority for all universities, the availability of programs to support the timely completion of PhD theses across Australian universities, is variable. Moreover, little is known specifically about the institutional support programs available for students undertaking a PhD in law, reasons for adopting chosen support programs, or how effective the programs that are available are in supporting students to successful and timely completions. The research study across select Australian universities reported on in this article sought to begin to close this knowledge gap. In doing so, it: 1) provides an overview and synthesis of the Australian and international literature on achieving timely PhD completions across disciplines; 2) presents the results from two surveys: a perceptions survey of students enrolled in PhD programs at Australian law schools; and a survey of the support programs offered at 16 Australian law schools; and 3) drawing on the conclusions from the literature and survey results, explores how best to support PhD students in law to successful and timely completions. Key conclusions emerged from this study relevant to both law PhD students and law schools. Overwhelmingly, the results indicate that the importance of a collegial and communicative supervisor cannot be overstated. Further, students who engage informally with other academics (such as PhD mentors) as well as their PhD peers are also more likely to complete. Overall, while acknowledging that, inevitably, personal characteristics and circumstances affect PhD success, we conclude that institutional level support may nonetheless contribute to timely completions in law.